2001
DOI: 10.2143/ac.56.5.2005689
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic function and baroreflex sensitivity during angiotensin-converting enzyme inhibition or angiotensin II AT-1 receptor blockade in essential hypertensive patients

Abstract: In hypertensive patients, the angiotensin system or bradykinins do not seem to have any modulatory effect on the sympathetic/parasympathetic control of blood pressure and baroreflex sensitivity, in a resting condition. Since heart rates were unchanged by the two antihypertensive treatments despite a significant reduction of blood pressure, a resetting of baroreflex function was observed during both ACE-inhibition and angiotensin II ATI receptor blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Concentration of serum angiotensin converting enzyme (ACE) and angiotensin II (Ang II) and plasma catecholamines viz . norepinephrine and epinephrine was also determined [31], [32].…”
Section: Introductionmentioning
confidence: 99%
“…Concentration of serum angiotensin converting enzyme (ACE) and angiotensin II (Ang II) and plasma catecholamines viz . norepinephrine and epinephrine was also determined [31], [32].…”
Section: Introductionmentioning
confidence: 99%
“…ARBs also decreased the low-tohigh-frequency ratio in hypertensive patients [ 44 ]. However, other reports, mostly in hypertensive patients, did not show any benefit of ARBs with regard tothese parameters [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. In addition, some studies reported an improvement in some parameters of cardiovascular autonomic function (i.e., baroreflex sensitivity), but not in others (i.e., HRV) [ 54 ].…”
Section: Studies Onnon-diabetic Patientsmentioning
confidence: 87%
“…Considering the paucity of studies in adult patients with ALL on chemotherapy, this study intends to evaluate the cardiac autonomic function and endothelial and inflammatory biomarker levels in adult patients with ALL, immediately after completion of chemotherapy and at three months after completion of chemotherapy. [12][13][14]. The study participants were followed for three months and 26 ALL patients were able to participate in the study at the end of three months because two male patients expired and two male patients went into relapse.…”
Section: Introductionmentioning
confidence: 99%